Ghosts on the loose - Beaudine, William, 1892-1970; Lugosi, Bela, 1882-1956; Gardner, Ava, 1922-1990; East Side Kids (Musical group); Monogram Pictures Corporation; Banner Productions; Cinetel Films ([Los Angeles, CA] : Monogram Pictures Corp. : Banner Productions, 1943)
Glimpy's surprisingly beautiful sister is getting married to Jack, a young engineer, and moving to a 'bargain' suburban house neither has ever seen. During the honeymoon, the East Side Kids decide to fix up the house for the newlyweds...but mistakenly pick the 'haunted' house next door, which is occupied by some mysterious live men, dodging in and out of secret panels and clearly up to no good... --
The East Side kids: Leo Gorcey, Huntz Hall, Bobby Jordan; and Bela Lugosi, Ava Gardner, Rick Vallin.
Photography, Mack Stengler; editor, Carl Pierson; musical director, Edward Kay
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 8, 2015)
Keywords: Bowery Boys films; Haunted houses -- Drama; Spies -- New York (State) -- New York -- Drama; World War, 1939-1945 -- United States -- Drama; Lower East Side (New York, N.Y.) -- Drama; Feature films; Comedy films; Internet videos; Streaming video